Rogue access point detector in UTAR campus - Kok, Ser Leen (2024)
In the current digital era, network security is an essential concern, especially given the growing usage of wireless networks. In contrast, network security may be vulnerable to rogue access points and unauthorised wireless access points that provide security threats. As wireless network technology constantly grows and evolves at a rapid pace, the use of this technology in various sectors including tertiary institutions is notably inevitable. The rapid growth and evolvement of wireless network technology has improved the quality of life of delivering data and the flexibility of using such technology, however, it has indefinitely also introduced new security challenges in particular the threat of Rogue Access Points (RAP). In addition, this project introduces an intelligent algorithm for RAP detection and an additional isolation feature, if implemented, it is expected to safeguard the internal network of the institutions from unauthorised intruders to gain private insights of the network. Additionally, a preliminary analysis of potential network security vulnerabilities will be carried out and the most recent research on RAP will be analysed and compared with the suggested method in a literature review. As a result, while creating a framework to reduce the threat of rogue access points in tertiary institutions, the idea of employing the proposed technique to do so may be taken into account.